Analysis of the Impact of Social Investment of PT Bank Central Asia, Tbk on the Tourism Village Improvement Program - Justin Saputra*; Farah Margaretha; Maria C Widiastuti (Universitas Syiah Kuala, 2024)
This study was conducted to analyze the impact of a social investment made by PT Bank Central Asia, Tbk on the improvement of tourist villages by calculating the cost-benefit analysis the rate of return on social investment, the contribution of the program to the achievement of Sustainable Development Goals, as well as the analysis of the creation of Corporate Social Innovation in the tourist village improvement program. The results of this study prove that the cost-benefit analysis and the rate of return on social investment show positive numbers, which means that the positive benefits created are greater than the costs/investments incurred for the improvement of tourist villages. In addition, the tourism village improvement program contributes to the 6 points of the Sustainable Development Goals, as well as corporate social innovation created from the dimensions of accessibility, amenity, and attractions including the addition of new tour packages and increasing visitors' awareness of waste. The HR, Community, and Industry dimensions, include innovation in improving services, as well as creating a memorable experience for visitors. The Branding, Advertising Selling dimension includes increasing creativity in promotion on social media. The managerial implication of this research is that the tourism village development program creates long-term changes for beneficiaries, such as increasing income, increasing the skills and knowledge of local communities, creating economic independence, encouraging the use of technology in the tourism village operation business, and creating social innovation in developing the attraction aspect of a tourism village. These changes in impact create a good relationship between the company and program stakeholders, where social investment programs directly provide business benefits for the company, and support the company's commitment to achieving ESG, especially in social aspects